Poetyckie remediacje Anety Kamińskiej - Winiecka, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article presents the works of Aneta Kamińska as an example of the phenomenon of remediation, it is the impact of digital media on poetry and literary communication. The authoress examines the subsequent volumes of poetry and forms of Kamińska’s online activity. She points at a specifically feminine approach to new technologies. The article describes changes in the structure of the poems, as well as the status of the authoress and the nature of her communication with readers. It discusses also the stages of Aneta Kamińska’s work. These are: the traditional volume, the volume imitating hypertext which has been partly digitized and is available online as an interactive poetic hypertext. Then discusses the impact of Internet communication on her poetry. Finally presents multimedia projects, in which words are combined with video, audio and animation. In the end we may ask the question: does the generator of poetry, used by the poet, open up the interaction between man and machines?